The effect of motivational video and nutrition on the non-stress test: a randomised controlled clinical trial. (18th August 2022) - Timur Taşhan, Sermin; İnci Coşkun, Ebru and Nacar, Gülçin and Erci, Behice
Abstract: This study aimed to determine the effect of motivational video stimulation and nutrition on the non-stress test (NST). The sample of the study consisted of 360 pregnant women in total, including two experimental groups and one control group (120 pregnant women in each group). After the pregnant women in the study were divided into three groups at a 1:1:1 ratio with the computer-assisted random sampling method, the draw method was used to determine the experimental and control groups. The pregnant women in the first experimental group were allowed to consume cake and juice 30 min before the NST procedure. The pregnant women in the second experimental group were also allowed to consume cake and juice, while they were also shown a video with the content of development and changes in the mother and the foetus during pregnancy, with relaxing music, for about 15–20 min. There was no intervention made in the control group. The data were collected using a Participant Information Form and an NST Findings Registry Form which were created by the researchers based on their review of the relevant literature. The data were analysed using arithmetic means, percentage distributions, ANOVA, Bonferroni and chi-squared tests. It was found that the mean number of foetal movements and the mean number of accelerations in the cake + juice and motivational video groups were higher than those in the control group ( p < 0.001). Besides, the pregnant women in the experimental groups were found to have more reactive NST results. As a result, it was determined that the motivational video and cake + juice interventions improved the movement of the foetus, the number of accelerations and the ratio of reactivity in NST, but the two interventions did not have any superiority over each other. It is recommended to offer cake and juice to pregnant women before NST or have them watch a motivational video during NST, for having good NST results. Impact statement: What is already known about the topic? The false-positive rates of the NST, which enables monitoring foetal movements and foetal heart rates, are high. These false-positive rates of the NST lead to many obstetric complications, in addition to increasing the rates of cesarean-section deliveries. Recent studies showed that there are methods and factors that increase foetal movements and shorten the application period of the NST. It was identified that food intake, music therapy, foetal vibroacoustic and halogen light stimulation before the NST increases foetal movements and shortens the application period of the NST. What this paper adds? In the study, it was found that watching motivational videos and consuming cake and juice increased the number of foetal movements, the number of accelerations and the rate of reactive NST results, but the two interventions did not have superiority over each other. What are the implications of these findings for clinical practice and/or further research? In order to increase reactive NST rates, it is recommended that pregnant women consume cake and fruit juice before the procedure and watch a motivational video during the NST procedure.